Toxoplasma gondii in semen of experimentally infected swine Toxoplasma gondii no sêmen de suínos experimentalmente infectados - Anderson B. Moura; Alvimar J. Costa; Sérgio Jordão Filho; Beatriz B. Paim; Fernanda R. Pinto; Daniela C. Di Mauro (Pesquisa Veterinária Brasileira, 2007)
Eight reproductive boars were divided into three groups and inoculated with Toxoplasma gondii [GI (n=3) 1.5x10(4) oocysts strain P; GII (n=3) 1.0x10(6) tachyzoites strain RH; and GIII (n=2) non-inoculated control]. Clinical, hematological, parasitemia and serological tests and studies of the parasite in the semen through bioassay and PCR, and in reproductive organs (Bioassay and immunohistochemical analyses) were conducted to evaluate the toxoplasmic infection. Blood and semen were collected on day -2, -1, 1, 3, 5, 7, 9, 11, 14 and weekly up to 84 days post-inoculation (DPI). No clinical or hematimetric alteration was observed in the boars. Parasitemia was detected in one boar inoculated with oocysts at the 7th DPI and in another boar infected with tachyzoites (GII) at the 3rd and 49th DPI. Serological tests revealed antibodies against T. gondii in animals inoculated with oocysts or tachyzoites at the 7th DPI with dilutions of 1:256 and 1:64, which reached peaks of 1:4096 at day 11 and 9, respectively. The bioassays revealed the presence of the parasite in semen samples of a boar inoculated with oocysts (GI) at 3, 49 and 56 DPI and from two boars infected with tachyzoites (GII), one animal at 5 and two animals at 49 days DPI. Mice inoculated with semen from the control group (GIII) remained serologically negative. PCR analysis showed T. gondii DNA in the semen of Boar 1 and Boar 3 inoculated with tachyzoites and oocysts, respectively. The immuno-histochemical tests showed T. gondii in the reproductive organs of Boar 1 and Boar 2, inoculated with tachyzoites and oocysts, respectively. These findings suggest the possible occurrence of venereal transmission of T. gondii in swine. Oito reprodutores suínos foram divididos em três grupos e inoculados com Toxoplasma gondii [GI (n=3) 1.5x10(4) oocistos cepa P; GII (n=3) 1.0x10(6) taquizoítos cepa RH, e GIII (n=2) controle, não inoculados]. Exames clínicos, hematológicos, de parasitemia e sorológicos foram realizados para avaliar a infecção toxoplásmica. Pesquisa do parasito no sêmen, por meio do bioensaio e pela técnica da PCR, e em órgãos do sistema reprodutor (bioensaio e imunohistoquímica) foi realizada. Sangue e sêmen foram colhidos nos dias -2, -1, 1, 3, 5, 7, 9, 11, 14, e semanalmente até o 84º dia pós-infecção (DPI). Nenhuma alteração clínica ou hematimétrica foi observadda nos animais. Parasitemia foi detectada em um animal inoculado com oocistos no 7º DPI e em outro inoculado com taquizoítos (GII) nos 3º e 49º DPI. A sorologia revelou a presença de anticorpos contra T. gondii nos animais inoculados com oocistos ou taquizoítos no 7º DPI com títulos de 1:256 e 1:64, que atingiram picos de 1:4096 nos dias 11 e 9, respectivamente. O bioensaio revelou a presença do parasita em amostras seminais de um animal inoculado com oocistos (GI) nos 3º, 49º e 56º DPI, e de dois animais infectados com taquizoítos (GII), um deles no 5º DPI e os dois ao 49º DPI. Pela PCR, o DNA de T. gondii foi detectado no sêmen dos Suínos 1 e 3 inoculados com taquizoítos e oocistos, respectivamente. A imunohistoquímica revelou T. gondii em órgão do aparelho reprodutor dos Suínos 1 e 2, inoculados com taquizoítos e oocistos, respectivamente. Esses achados sugerem a possibilidade da ocorrência da transmissão venérea do T. gondii em suínos.